Micropropagação e diversidade genética em Apuleia leiocarpa (Vogel) J. F. Macbride - Lencina, Kelen Haygert (2016)
The aim of this study was to evaluate the in vitro productivity of micro-stumps, in vitro and ex vitro rooting and acclimatization of micropropagated plantlets, and to assess the genetic diversity of Apuleia leiocarpa (Vogel) J. F. Macbride (apuleia) with RAPD markers. Micro-stumps originated from drastic pruning of aseptic seedlings were grown in WPM culture medium supplemented with 0; 2.2; 4.4; 6.6 and 8.8 μM of 6-benzylaminopurine (BAP) and sub-cultured in WPM medium without cytokinin. Apuleia micro-stumps were also grown in WPM, MS or ½ MS, with or without 1.5 g L-1 of activated charcoal. Three shoot collections were done at 30, 60 and 90 days of cultivation. Nodal segments and micro-cuttings were maintained in WPM culture medium with 0; 4.9; 9.8; 14.7 and 19.6 μM of indole butyric acid (IBA). For acclimatization, rotted nodal segments and micro-cuttings were planted in equal proportions of commercial substrate + vermiculite + coarse sand, and commercial substrate + vermiculite. For ex vitro rooting, nodal segments and micro-cuttings were treated or not with 4920 μM of IBA for 10 seconds and cultivated in equal proportions of commercial substrate + vermiculite + coarse sand, commercial substrate + vermiculite, and commercial substrate + coarse sand. For genetic analysis, DNA was extracted from leaf samples of 88 plants of apuleia. Eighteen RAPD primers were tested. The amplified fragments were separated in agarose gel of 1.2% (v/v), containing 3 μL of ethidium bromide. The fragments were marked as absence or presence, generating a binary matrix. Total polymorphism and the relative contribution of each primer for the polymorphism were calculated. The polymorphism information content (PIC) was calculated for each fragment and primer. Cluster analysis was based upon Jaccard similarity and UPGMA method. The conservation of the apuleia micro-stumps in WPM or ½ MS media supplemented with 8.8 μM of BAP and sub-cultured in culture medium without citokynin increases number and length of shoots. Maintaining micro-stumps in culture medium supplemented with activated charcoal increases micro-cuttings production, but in its absence results in callus formation and indirect organogenesis of shoots. Nodal segments were more competent than micro-cuttings for rooting in culture medium without IBA. Substrate composition does not affect survival and growth during acclimatization of in vitro produced plantlets. Nodal segments treated with 4920 μM of IBA and cultivated in commercial substrate + vermiculite + coarse sand show the best responses for ex vitro rooting. Both in vitro conservation of apuleia micro-stumps and ex vitro rooting are promising strategies for plantlet production. The RAPD is a feasible technique for genetic analysis, and it identifies high genetic variability in apuleia.